Image and implementation of sustainable urban development: showcase projects and other projects in Freiburg, Heidelberg and Tübingen, Germany = Image und Umsetzung nachhaltiger Stadtentwicklung - Growe, Anna; Freytag, Tim (Raumforschung und Raumordnung, 2019)
The principles of sustainability are currently applied in Germany and many other countries as important guidelines for urban development. However, different forms of understanding regarding sustainable development and different approaches concerning its implementation can be found in various spatial contexts. This paper focuses on Freiburg, Heidelberg and Tübingen, three cities in southwestern Germany. These cities produce different images due to ambitious urban development plans which are based on the three pillars of ecological, economic and social sustainability in different ways. Numerous similarities between these three cities notwithstanding, they highlight different aspects of sustainable urban development and emphasise them via particularly widespread awareness of ‘showcase projects’. For Freiburg, this includes Vauban and Rieselfeld, for Heidelberg Bahnstadt, and for Tübingen Französisches Viertel and Loretto. The central questions in this paper are therefore: How do images and the implementation of sustainability differ with regard to the three pillars of sustainability? How can differences and similarities with regard to the three pillars of sustainability be explained and what consequences can be drawn for future studies in sustainable urban development? Following a classification of research perspectives on sustainable urban development, distinguishing between more practically oriented aspects, on the one hand, and theory-based critical considerations, on the other, this article examines showcase projects from the three selected cities on the basis of planning documents, websites, local newspapers and academic literature. Moreover, further projects are taken into consideration. The paper concludes with general observations and discussions concerning the image and implementation of sustainable urban development.
Literaturverzeichnis: Seite 472-474